Bioaccumulation of Heavy Metals Lead, Copper, and Zinc in Mangrove Roots Avicennia marina, Water, and Sediment in Panceng Waters, Gresik, Jawa Timur - Diyah Retnosari, Fenny; Andriyono, Sapto; Nurmalia Dewi, Nina (Universitas Airlangga, 2024)
Panceng water is a coastal area that has quite a lot of activities, and this can trigger an increase in waste pollution. This polluting waste can cause an increase in the bioaccumulation of heavy metals in waters. Therefore, this research aims to obtain information on environmental management monitoring activities, such as water quality conditions by determining the concentration of heavy metals Pb, Cu and Zn in the roots of the Avicennia marina mangrove, water and sediment in Panceng Waters, Gresik. The method used was observation, examination of the heavy metals Pb, Cu, and Zn using ICP-MS, and the data was analyzed using quantitative descriptive methods. The results of the analysis of the concentration of the heavy metal Pb in the roots of the mangrove averaged 0.3 mg/kg, Cu 1.205 mg/kg and Zn 0.14 mg/kg. The concentration of heavy metals Pb in sediment was 5.49 mg/kg, Cu 15.7 mg/kg, and Zn 30.6 mg/kg. Meanwhile, the concentration of heavy metals Pb, Cu and Zn in sea water was not detected (ND). Overall water and sediment are still below the threshold. However, the concentration of heavy metals in the roots of the A. marina mangrove is relatively high, above the quality standards of Minister of Environment Decree No. 22 of 2021. Calculation of the level of heavy metal pollution based on Enrichment Factor (EF), Geo-Accmulation Index (Igeo) and Contamination factor (CF) values shows that the heavy metals Pb, Cu and Zn indicate levels of pollution and contamination that are still low to moderate. The Bio Concentration Factor (BCF) of A. marina in Panceng Waters, Gresik is included in the excluder category (BCF<1). The results of this research indicate that the A. marina mangrove can be developed as a phytoremediation agent because it is able to absorb and transfer heavy metals from the environment to other body tissues.